Revitalizing cross-border cooperation in West Africa: the example of the Benino-Nigerian border in the light of Franco-Spanish cooperation - (:unkn) unknown (My University, 2023)
West Africa is the region that covers the entire western part of sub-Saharan Africa. There are French-speaking countries (8), English-speaking countries (5) and Portuguese countries (2). For practical reasons, I am currently focusing on two countries in this region, namely Benin and Nigeria. I chose these two countries for the problems of irredentism, of demarcation that they had. Therefore, the cross-border cooperation that is developing at that border is not up to our expectations. In addition, they are part of an institution called ECOWAS, which functions like the European Union (EU). This case of cross-border cooperation between Benin and Nigeria has certain characteristics similar to those of the Franco-Spanish case.
Keywords: African Research